Enantioseparation of dansyl amino acids in capillary electrophoresis using a novel chiral selector : mono-6-deoxy-6-(ethanolammonium)-β-cyclodextrin. - Selvi Ramaswami. (2012)
A positively charged novel single isomer β-CD was synthesized through nucleophilic substitution of Mono-6-tosyl-β-CDs with Ethanolammonium to give Mono-6-deoxy-6- (Ethanolammonium)-β-cyclodextrin tosylate, followed by anion exchange to produce the chiral selector Mono-6-deoxy-6-(Ethanolammonium)-β-cyclodextrin chloride (EtAM-β- CDCl). The cationic CD was analytically characterized and their chiral resolution ability was studied with Capillary Electrophoresis using dansyl (Dns)-Amino acids as model analytes in acidic aqueous BGE. The concentration of the chiral selector and the pH of the BGE were varied extensively from 6 to 15mM and pH (6.5 to 8.5) respectively to understand their influence on the resolution and selectivity of the cationic CD. From the experiment results, it was seen that the chiral resolution increased with increase in CD concentration and reached optimum at 10mM, but decreased with increase in pH, with the prime at pH 6.5. The electrostatic interaction along with the inclusion complex formation seemed to account for the effective separation of the analytes. Further the fivedansyl amino acid mixture was enantioseparated using EtAM-β-CDCl as chiral selector.